Rift-related volcanism predating the birth of the Rheic Ocean - Sanchez-Garcia, Teresa (2010)
Two very different periods of magma emplacement in the crust of the Ossa-Morena zone (early and main events) in SW Iberia have been previously interpreted to record a Cambrian/Early Ordovician rifting event that is thought to have culminated in the opening of the Rheic Ocean during the Early Ordovician. New stratigraphic, petrographic, geochemical and Sm–Nd isotope data from Cambrian volcanic rocks included in six key low-grade sections in both Portugal and Spain considerably improve our understanding of these events. These data: (1) confirm the existence of two rift-related magmatic events in the Cambrian of the Ossa-Morena zone, (2) demonstrate that the early rift-related event was associated with migmatite and core-complex formation in the mid-upper crust and is represented by felsic peraluminous rocks, the parent magmas of which were derived mainly from crustal sources, and (3) show the main rift-related event to be represented by a bimodal association of felsic and mafic rocks with minor amounts of intermediate rocks. Some of the mafic rocks show N-MORB affinity, whereas others have OIB or E-MORB affinities, suggesting different heterogeneous mantle sources (depleted and enriched, asthenospheric and lithospheric, plume-like and non-plume-like). The acid and intermediate rocks appear to represent hybrid mixtures of crust and mantle-derived magmas. This new data supports the hypothesis that the onset of rifting was associated with a process of oblique ridgetrench collision. We interpret the significant differences between the early and main events as reflecting the evolution froma wide rift stagewith passive extensionmainly accommodated by lower-crust flowin a high heatflow setting, to a narrow rift stage with active extension characterized by extension rates that outpaced thermal diffusion rates.